Maxillary Sinus Floor Augmentation With or Without Barrier Membrane Coverage of the Lateral Window: a Systematic Review and Meta-Analysis - Thomas Starch-Jensen; Daniel Deluiz; Kirsten Duch; Eduardo Muniz Barretto Tinoco (Stilus Optimus, 2019)
Objectives: Test the hypothesis of no difference in implant treatment outcomes after maxillary sinus floor augmentation with or without barrier membrane coverage of the lateral window. Material and Methods: A MEDLINE (PubMed), Embase and Cochrane library search in combination with a hand-search of relevant journals was conducted. Human studies published in English until the 5th of July, 2019 were included. Randomised controlled trials and controlled trials with an observation period of minimum six months were included. Primary outcomes included survival of suprastructures and implants. Secondary outcomes included implant stability quotient, peri-implant marginal bone loss, bone regeneration, patient-reported outcome measures, biologic and mechanical complications. Results: The electronic search and hand-searching resulted in 1068 entries. Six randomised controlled trials characterised by low to high risk of bias and one controlled trial with high risk of bias fulfilled the inclusion criteria. High implant survival rate was reported with both treatment modalities. Meta-analyses disclosed a mean difference of newly formed bone of 6.4% (confidence interval = 0 to 12.9) and non-mineralised tissue of -1.1% (confidence interval = -2.7 to 0.5), indicating more newly formed bone and diminished non-mineralised with barrier membrane coverage. Conclusions: There seem to be no statistically significant differences in implant treatment outcomes after maxillary sinus floor augmentation with or without barrier membrane coverage of the lateral window. However, barrier membrane coverage increases percentage of newly formed bone and diminishes proliferation of non-mineralised tissue. Thus, barrier membrane coverage seems to be beneficial and also preventing displacement of the grafting material.